DEVELOPMENT OF CONCEPT “SOCIALIZATION” IN PEDAGOGICAL WORKS OF TEACHERS DURING PERIOD OF XIX – XX AGE - Sivak, Nataliia (Continuing Professional Education: Theory and Practice, 2019)
The development and becoming of socialization as a social pedagogical concept in a period XIX-XX of age is exposed in the article; the attention is concentrated and works of teachers, psychologists of the noted period, are analyzed in relation to expansion of essence and maintenance of concept socialization: constituents, mechanisms, law conformities, levels, factors of socialization, as a process; roles of society, education and heredity, are in the noted process. So ideas the analysis of which grounds us to talk about expansion of approaches teachers in relation to socialization of personality appear in works of teachers in the middle of XIX age: the unity of school, state, church, clubs, social organizations; relations between basic agents; the use of game and labor is in the process of introduction a man to socium. it should be noted that teachers of this period, examining personality in the process of socialization from the point of authentication and interiorizacion, is specified on bilateralness of socialization, in which a man occupies active position and influences on different social processes. Psychological bases of socialization are opens up in works of psychologists. Works of teachers are analyzed in relation to expansion of maintenance of socialization by a concept “self-realization”.